DIVERSITY ADULT AGE LIMITS POSITIVE LAW IN INDONESIA (Studies in Multidisciplinary Perspective) - Muhammad Andri (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Maturity has always been a responsibility of the size of a deed. Since only an adult is considered perfectly justifiable actions, but in some fields of science in practice there are differences in maturity parameters. This we can see from some of the provisions of the law which provides qualifications on works which in principle can only be done by those who have grown up. This type of research is a normative legal research includes studies of the principles of law or legal doctrine, technique of data collection is done with the study of literature in the form of documents or activities to collect and inspect, examine documents this be required. Research answering the problem formulation: why adults boundary conditions according positive law specified 21 years but from a wide range of existing regulations show the differences between one another. And what about the legal issues arising from the diversity of the legal adult age. the results of this study show that the legal system in Indonesia in general, there is disparity in the adult limit. Among the provisions is one to the other there is a correlation when the scope it governs have a point of tangency and the close linkage relationship. Supposedly every law that each other can be complementary and mutually close any vacancy that exists, but is actually giving each overlapping rules on the same subject, it is this which creates inconsistencies in the law enforcement and implementation of laws in the field , The need for re-assessment and research on determining the legal adult age by using an approach through a variety of disciplines in order to get the limited ability that is relevant to all disciplines; Keywords: age limits, legal competence, maturity